Use of Three Air Samplers for the Detection of PRRSV-1 under Experimental and Field Conditions - Stein, Heiko (Animals (Basel), 2018)
SIMPLE SUMMARY: Respiratory diseases are of particular importance in pig production since they influence productivity, animal welfare and consumer protection. One of the most important respiratory diseases in pigs is caused by the porcine reproductive and respiratory syndrome virus (PRRSV). This virus, which can be divided into two separate species (PRRSV-1 and PRRSV-2), is causing high economic losses in the swine industry but does not represent a threat to humans, who cannot be infected with the virus. Airborne transmission of PRRSV has been reported to occur in PRRSV-2 isolates, but hardly any reports exist about airborne transmission of PRRSV-1. Therefore, we assessed three different air sampling systems for their ability to collect PRRSV-1 both under experimental conditions and in the field. First, we vaporized PRRSV-1 in an experimental chamber by a fogging device. Then, we tested the same air samplers under field conditions in a PRRSV-1 positive pig farm. Under experimental conditions all three air sampling systems were able to detect PRRSV-1. However, all three systems failed to detect PRRSV-1 under field conditions. ABSTRACT: Airborne transmission of porcine reproductive and respiratory syndrome virus (PRRSV) has been known for a long time. Most experiments were performed using PRRSV-2 strains and fairly little information is available on the airborne spread of PRRSV-1. The aim of this study was to assess three different air samplers for their ability to detect PRRSV-1 under experimental and field conditions. All three devices were able to detect PRRSV-1 by quantitative reverse trascription polymerase chain reaction (qRT-PCR) under experimental conditions. However, the detection of PRRSV-1 in a PRRSV-positive farm with active virus circulation was not successful.